Chronic Inflammation After Severe Traumatic Brain Injury: Characterization and Associations With Outcome at 6 and 12 Months Postinjury. Issue 6 (November 2015) - Kumar, Raj G.; Boles, Jennifer A.; Wagner, Amy K.
Abstract : Objective: Examine associations between chronic inflammatory profiles and outcome 6 to 12 months following severe traumatic brain injury (TBI). Setting: University-affiliated level 1 trauma center and community. Participants: Adults with severe TBI ( n = 87); healthy controls ( n = 7). Design: Prospective cohort study. Main Measures: Glasgow Outcome Scale; serum cytokines (interleukin [IL]-1β, IL-4, IL-5, IL-6, IL-7, IL-8, IL-10, IL-12, tumor necrosis factor α), 2 weeks to 3 months, 4- to 6-month averages, 6- and 12-month levels. Results: Serum levels of IL-1β, IL-6, IL-8, IL-10, and tumor necrosis factor α were elevated over 3 months following TBI. Multivariate analysis showed that increased cytokine load score was associated with a 1.21 (95% confidence interval, 1.06-1.38) and 1.18 (95% confidence interval, 1.02-1.37) increase in odds of unfavorable Glasgow Outcome Scale score at 6 and 12 months, respectively. Also, elevated IL-6/IL-10 ratios were associated with increased odds of unfavorable outcomes at 6 months (adjusted odds ratio = 1.76; 95% confidence interval, 1.08-2.88). Conclusions: Chronic inflammation has not been well characterized following TBI. Our subacute cytokine load score classifies individuals at risk for unfavorable outcomes following injury. Higher proinflammatory burden with IL-6, relative to the anti-inflammatory marker IL-10, is significantly associated with outcome. Further research should examine whether inflammatory genes and other inflammatory biomarkers affect risk for unfavorable outcomes and TBI complications.